Priming intramodal and intermodal: a gustatory -visual study - Razumiejczyk, Eugenia (2008)
The aim of this study is to evaluate within and across priming between taste and vision. The data showed a facilitation in recognition of studied stimuli in relation to new stimuli in the experiment of within priming. In the experiments of within and across priming, the recognition of the studied stimuli did not differ significantly from the recognition of new stimuli. In both studies, the results showed that the processing time required to recognize studied stimuli were smaller than the time required for new stimuli. There was a negative correlation between processing time and recognition. The occurrence of within and across priming between taste and vision are consistent with the evidence of this studies.